2022
DOI: 10.3390/polym14030563
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mechanical Properties of Graft-Type Nanocomposites Using Organically Modified SiO2 and Polypropylene Containing Reactive Methoxy Groups

Abstract: In situ grafting of a reactive matrix and nanofillers is a promising strategy to fabricate graft-type polypropylene (PP)-based nanocomposites, where the grafting efficiency is affected by the initial dispersion of nanofillers in the matrix. In this work, influences of surface organic modification of nanofillers were investigated on properties of PP/SiO2 nanocomposites using poly(propylene-co-octenyltrimethoxysilane) as a reactive matrix. The surface modification of SiO2, especially with longer alkyl chains, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Therefore, it is difficult to directly form a dense and defect-free PA layer on such a substrate. There are various methods to hydrophilize the substrates, such as surface coating, chemical grafting, and layer-by-layer assembly. The introduction of hydrophilic additives during the electrospinning process is a convenient and effective method of fabricating hydrophilic membranes. The hydrophilicity can be controlled by the contents of the additives.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is difficult to directly form a dense and defect-free PA layer on such a substrate. There are various methods to hydrophilize the substrates, such as surface coating, chemical grafting, and layer-by-layer assembly. The introduction of hydrophilic additives during the electrospinning process is a convenient and effective method of fabricating hydrophilic membranes. The hydrophilicity can be controlled by the contents of the additives.…”
Section: Resultsmentioning
confidence: 99%
“…The grafted silane molar percentage (Ms %) on NMs can be calculated as follows Equation ( 2): [123] Where Mw silane and Mw NMs are the molecular weight of silane and NMs, respectively, ~m is the weight loss from the TGA in specific temperature range, r a/s the molecular weight ratio of the alkyl chain versus the whole silane molecule. By having Ms (%) and using following Equation (3), we can obtain Grafting density: [123,124] D. Zhu et al reported the surface modification of SiO 2 using different silanes (Trichlorohexylsilane, trichlorododecylsilane, and trichloro-hexadecylsilane) with alkyl chain lengths of C6, C12, and C16, respectively. [124] The results indicated that at a fixed mole of silane coupling agents (0.1 mmol), the grafting density decreased with an increase in the alkyl chain length.…”
Section: Figure 20mentioning
confidence: 99%
“…By having Ms (%) and using following Equation (3), we can obtain Grafting density: [123,124] D. Zhu et al reported the surface modification of SiO 2 using different silanes (Trichlorohexylsilane, trichlorododecylsilane, and trichloro-hexadecylsilane) with alkyl chain lengths of C6, C12, and C16, respectively. [124] The results indicated that at a fixed mole of silane coupling agents (0.1 mmol), the grafting density decreased with an increase in the alkyl chain length. It is considered that the adsorption and reaction of a molecule of a bulky silane-coupling agent inhibit the approach of a new molecule to the surrounding silanols.…”
Section: Figure 20mentioning
confidence: 99%
“…Therefore, it is an issue to synthesize uniform and integral polyamide layers on hydrophobic substrates via interfacial polymerization. To overcome this obstacle, researchers have developed various surface modification methods to hydrophilize the substrates, such as surface coating, vapor deposition, plasma treatment, , chemical treatment, grafting, and layer-by-layer assembly. , Among these methods, some are limited by the complex operational process, specific devices, or high energy-consumption. Surface coating has been considered as a promising strategy for the characteristics such as simplicity, conformal modification, and easy to large-scale fabrication.…”
Section: Introductionmentioning
confidence: 99%